2000
DOI: 10.1053/jpro.2000.21157
|View full text |Cite
|
Sign up to set email alerts
|

The ocular impression: A review of the literature and presentation of an alternate technique

Abstract: Improved fit is one advantage of a custom ocular prosthesis. Numerous methods exist to gain intimate tissue adaptation. This article reviews the literature concerning such methods and presents an improved technique for fabrication of a custom ocular impression tray. J Prosthodont 2000;9:210-216. This is a US government work. There are no restrictions on its use. INDEX WORDS: artificial eye, custom impression tray From Wilford Hall

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 13 publications
0
26
0
7
Order By: Relevance
“…A eficácia e escolha de cada método dependem da experiência do profissional e dos materiais disponíveis 9 . No presente relato clínico, foi utilizada a técnica descrita por Mathews et al 10 Bartlett e Moore 11 e Maia et al 6 na qual a moldagem é realizada através da injeção do material com seringa plástica e com moldeira individual de resina acrílica, perfurada com uma adaptação de um conduto central para acoplar a seringa, confeccionada a partir da prótese ocular do próprio paciente.…”
Section: Discussionunclassified
“…A eficácia e escolha de cada método dependem da experiência do profissional e dos materiais disponíveis 9 . No presente relato clínico, foi utilizada a técnica descrita por Mathews et al 10 Bartlett e Moore 11 e Maia et al 6 na qual a moldagem é realizada através da injeção do material com seringa plástica e com moldeira individual de resina acrílica, perfurada com uma adaptação de um conduto central para acoplar a seringa, confeccionada a partir da prótese ocular do próprio paciente.…”
Section: Discussionunclassified
“…A custom‐made ocular prosthesis replicates the orientation, natural color, contour, and size of the pupil and iris, providing realism and symmetry to the patient's face. In addition, it improves the fit of the prosthesis by gaining the intimate tissue adaptation 17 . Positioning of the iris is an important step in fabrication of the custom‐made ocular prosthesis, which helps achieve better esthetics and self‐esteem of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…A number of techniques have been advocated for achieving optimal fit of ocular prostheses, such as the direct impression/external impression, use of a stock ocular tray, modification of a stock ocular tray, use of a custom ocular tray, an impression using a stock ocular prosthesis, ocular prosthesis modification, and the wax scleral blank technique . However, we have observed that clinically all these techniques cause discomfort for the patient during the fitting process.…”
mentioning
confidence: 88%